The Role and Significance of the Use of Wood Materials in the Architecture and Construction of Traditional Houses of the Indigenous Peoples of Uzbekistan - D.Z. Saloxiddinova; Z. Z. Zhuraev (Peerian Journals Publishing, 2022)
The article deals with issues, features of the use of wood materials in architecture and construction of traditional residential buildings. Provides information about the use of wood in architecture and construction of traditional ladies. The course of creation of the main constructive and structural wooden parts in traditional residential buildings is briefly disclosed. At the same time, the use of wood and wooden structures in the modern architecture of Uzbekistan is briefly disclosed
Keywords: Woodworking; Columns; Purlins; Racks